Endopeptidase O promotes Streptococcus suis immune evasion by cleaving the host- defence peptide cathelicidins - Mingjie Jin; Siyu Liang; Jing Wang; Huihui Zhang; Yueling Zhang; Wanjiang Zhang; Siguo Liu; Fang Xie (Virulence, 2023)
Streptococcus suis is a zoonotic Gram-positive bacterium that causes invasive infections such as sepsis and meningitis, threatening public health worldwide. For successful establishment of infection, the bacterium should subvert the innate effectors of immune defence, including the cathelicidin family of host-defence peptides that combat pathogenic bacteria by directly disrupting cell membranes and coordinating immune responses. Here, our study shows that an extracellular endopeptidase O (PepO) of S. suis contributes to assisting the bacterium to resist cathelicidin-mediated killing, as the deletion of the pepO gene makes S. suis more sensitive to the human cathelicidin LL-37, as well as its mouse equivalent, mCRAMP. This protease targets and cleaves both LL-37 and mCRAMP, degrading them into shorter peptides with only a few amino acids, thereby abrogating their ability to kill S. suis. By cleaving LL-37 and mCRAMP, PepO impairs their chemotactic properties for neutrophil migration and undermines their anti-apoptosis activity, which is required for prolonging neutrophil lifespan. Also, PepO inhibits the ability of LL-37 and mCRAMP to promote lysosome development in macrophages. Moreover, the loss of PepO attenuates organ injury and decreases bacterial burdens in a murine model of S. suis bacteraemia. Taken together, these data provide novel insights into the role of the intrinsic proteolytic characteristics of PepO in S. suis-host interaction. Our findings demonstrate that S. suis utilizes the PepO protease to cleave cathelicidins, which is an immunosuppressive strategy adopted by this bacterium to facilitate pathogenesis.